2010
DOI: 10.1007/s00436-009-1705-5
|View full text |Cite
|
Sign up to set email alerts
|

T cell reactions of Eimeria bovis primary- and challenge-infected calves

Abstract: Eimeria bovis infections commonly have clinical impact only on young animals, as homologous reinfections generally are under immunological control. So far, the nature of the immune responses delivering protection to calves has not been investigated. In this study we therefore analysed local and peripheral proliferative T cell activities of primary and challenge-infected calves and investigated the occurrence of T cell phenotypes in the peripheral blood and in mucosal gut segments isolated either by bioptic mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…However, the numbers of animals used were similar to previous studies (e.g. Hermosilla et al 1999;Sühwold et al 2010) and the combinations of high p values and lack of any hint of biologically meaningful trends suggests that the results are likely a legitimate reflection of similar status in the two groups as far as cellular infiltration is concerned. Eosinophils were more common in the ileum and colon of animals classified as resistant, and tended to be associated with higher concentrations of TNF-a.…”
Section: Figmentioning
confidence: 54%
See 3 more Smart Citations
“…However, the numbers of animals used were similar to previous studies (e.g. Hermosilla et al 1999;Sühwold et al 2010) and the combinations of high p values and lack of any hint of biologically meaningful trends suggests that the results are likely a legitimate reflection of similar status in the two groups as far as cellular infiltration is concerned. Eosinophils were more common in the ileum and colon of animals classified as resistant, and tended to be associated with higher concentrations of TNF-a.…”
Section: Figmentioning
confidence: 54%
“…In their study, there was no evidence of any memory-associated Th1 reactions to challenge infections. The same group (Sühwold et al 2010) has also shown that after an initial expansion of CD4+ T cells and gd+ T cells in the gut of animals after primary infection there was no increased infiltration of either cell type after challenge infection. The phagocytosis of Eimeria by macrophages has also been clearly demonstrated in cattle, independent of the presence of immune serum (Behrendt et al 2008) and augmented by immune serum (Taubert et al 2009).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The frequencies of the two other most prevalent species (E. arloingi and E. ninakohlyakimovae) increased thereafter but remained longer in time in contrast to E. christenseni, which might indicate a correlation with the farm history of sustained clinical coccidiosis observed in the farm in goat kids during the weaning period. The particularities of the life cycle, the virulence and the innate/acquired cellular immune response developed by the host against the different parasitic stages of each Eimeria species could explain those differences as reported for bovine coccidiosis (Hermosilla et al 2002;Daugschies and Najdrowski 2005;Taubert et al 2009;Sühwold et al 2010).…”
Section: Resultsmentioning
confidence: 92%